The effects of combined transcranial brain stimulation and a 4-week visuomotor stepping training on voluntary step initiation in persons with chronic stroke—a pilot study - Tseng, Shih-Chiao; Cherry, Dana; Ko, Mansoo; Fisher, Steven R.; Furtado, Michael; Chang, Shuo-Hsiu (Frontiers in Neurology, 2024)
Purpose: Evidence suggests that transcranial direct current stimulation (tDCS) can enhance motor performance and learning of hand tasks in persons with chronic stroke (PCS). However, the effects of tDCS on the locomotor tasks in PCS are unclear. This pilot study aimed to: 1) determine aggregate effects of anodal tDCS combined with step training on improvements of the neural and biomechanical attributes of stepping initiation in a small cohort of persons with chronic stroke (PCS) over a four-week training program; and 2) assess the feasibility and efficacy of this novel approach for improving voluntary stepping initiation in PCS. Methods: A total of 10 PCS were randomly assigned to one of two training groups, consisting of either 12 sessions of VST paired with a-tDCS (n=6) or sham tDCS (s-tDCS, n=4) over four weeks, with step initiation (SI) tests at pre-training, post-training, one-week and one-month follow-ups. Primary outcomes were: baseline vertical ground reaction force (B-vGRF), response time (RT) to initiate anticipatory postural adjustment (APA), and the retention of B-VGRF and RT. Results: a-tDCS paired with a four-week VST program results in a significant increase in paretic weight loading at one-week follow up. Furthermore, a-tDCS in combination with VST led to significantly greater retention of paretic BWB compared with the sham group at one week post-training. Clinical Implications: The preliminary findings suggest a four- week VST results in improved paretic limb weight bearing (WB) during SI in PCS. Furthermore, VST combined with a-tDCS may lead to better retention of gait improvements (NCT04437251).